1998
DOI: 10.2307/2446512
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics and taxonomic status of the rare Kentucky lady's slipper: Cypripedium kentuckiense (Orchidaceae)

Abstract: Cypripedium kentuckiense is a recently described rare orchid found in Arkansas (predominantly) and in eight other states. Much debate has focused on whether this taxon should be recognized as a distinct species or considered to be an extreme manifestation of the variability present in the widespread taxon Cypripedium parviflorum var. pubescens. In this study, 12 isozyme loci were analyzed for 14 populations of C. parviflorum var. pubescens and eight populations of C. kentuckiense. These data were used to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
3
25
1
2
Order By: Relevance
“…1998). This was also noted for other orchids (Scacchi et al . 1991; Ackerman & Ward 1999; Wong & Sun 1999; Gustafsson 2000).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…1998). This was also noted for other orchids (Scacchi et al . 1991; Ackerman & Ward 1999; Wong & Sun 1999; Gustafsson 2000).…”
Section: Discussionsupporting
confidence: 82%
“…In seven out of eight Estonian populations of this species (Kull & Paaver 1997) the level of H O were much higher ( H O = 0.40–0.53) than in the Biebrza valley populations ( H O = 0.151). It seems, that the genetic variation within Cypripedium genus, and in different populations of a given species belonging to this genus can vary substantially (Case et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Significant heterogeneity in the genetic structure of orchid populations was recently documented in a comprehensive review by Forrest et al (2004) with G ST estimates ranging from 0.012 to 0.924. Forrest et al (2004) reported a mean G ST estimate of 0.187 for all studies, higher than the respective averages of 0.159 and 0.087 reported earlier for orchids by Case et al (1998) and Hamrick and Godt (1996), but still lower than the mean G ST for other predominantly herbaceous families. Given that these data account for only a small number of studies, across a diverse set of orchid taxa, and that almost 80% of these data are based on allozyme studies, a technique that may underestimate genetic diversity, it is difficult to derive general patterns and advise conservation recommendations across the family.…”
Section: Introductioncontrasting
confidence: 72%
“…Several aspects of conservation biology, such as loss of genetic diversity in conservation program and restoration of threatened populations, can only be addressed by detailed population genetic studies (Hamrick and Godt, 1996). Nevertheless, studies on conservation genetics of orchid species are poorly represented in the literature although efforts have been made in recent decades toward this direction (Case, 1993;Case et al, 1998;Ackerman and Ward, 1999;Borba et al, 1999;Wong and Sun, 1999;Ehlers and Pedersen, 2000;Gustafsson 2000;Sun and Wong, 2001;Li et al, 2002;Li and Ge, 2006).…”
Section: Introductionmentioning
confidence: 99%